HIGHER ORDER KORTEWEG-DE VRIES MODELS FOR INTERNAL WAVES - JAHARUDDIN, J. (MILANG Journal of Mathematics and Its Applications, 2003)
By using asymptotic methods, evolution equation is derived for the internal waves in density stratiﬁed ﬂuid. This evo- lution equation arise as a solvability condition. A higher-order extension of the familiar Korteweg-de Vries equation is produced for internal waves in a density stratiﬁed ﬂow with a free surface. All coeﬃcients of this extended Korteweg-de Vries equation are expressed via integrals of the modal function for the linear theory of long internal waves.